Os evangélicos e a política no Brasil: posições, alinhamentos e tensões (1960-1976) - Machado, Adriano Henriques (2016)
This paper analyzes the political activities of Evangelicals, the "awakening" lived for them in strong effervescence period in the early 1960s, as well as their positions, disputes and tensions across the civil-military coup of 1964 and before the authoritarian regime to the year 1976, with special attention to the conservative offensive in this context emerged as a reaction to engagement proposals and political participation of churches in "Brazilian reality". The study focuses its analysis on the trajectory of two evangelical groups: the Methodist Church of Brazil (IMB) and the Baptists linked to the Brazilian Baptist Convention (CBB); having as main source journals produced by these names, in particular its two official bodies, respectively Expositor Cristão (EC) and O Jornal Batista (OJB). In order to broaden the understanding of their positions forward to change processes, continuities and ruptures occurred in the sociopolitical sphere, built on the dynamics of tensions and infighting of the two denominations, the relationship between them and the other evangelical groups, was used also the following publications: 1) the magazines produced by the youth of these churches, the Cruz de Malta (CM) and the Juventude Batista (JB); 2) periodic connected to the ecumenical movement groups, especially Boletim Ecumenical Information Centre (CEI) and Cristianismo newspaper; 3) other than those arising in the period after the coup, as Brasil Batista and Cristianismo Hoje. In consultation with the internal documentation of Churches, the Convention its Proceedings, conferences and congresses have also helped to discuss and understand the dynamics of political and ecclesiastical life of these institutions. The thesis is organized around two parts: the first, which includes the early 1960s and has as focus of analysis the growth process of the sectors that defended the "awakening" of the evangelical for participation in socio-political issues, including the how they were articulated and established relationships with other groups and on the proposals and ideologies that were on the political agenda of that period; and a second, which examines how evangelicals positioned themselves before the military regime, with a view to re-articulation of forces occurred in this segment, which made the reactionary-conservative groups, favored by authoritarian climate of the time, initiate an offensive for control political ideology of produced periodicals, as well as the spaces and internal structures of these institutions